Determination of lemon and carbonate effects on caffeine content of various teas and investigation of daily caffeine intakes - Demir, Funda; Kipcak, Azmi Seyhun; Ozdemir, Ozgul Dere; Piskin, Mehmet Burcin; Derun, Emek Moroydor (WALTER DE GRUYTER GMBH, 2016)
Objective: Tea (Camellia sinensis), has been used for health field in thousands of years. Caffeine is one of the key component in tea and investigation of caffeine is a popular working subject among the researches. The novelty of this study is not only the determination of the caffeine contents of the teas, but also how addition of lemon and carbonate effects the caffeine contents. Another aim of the study is the investigation of the daily caffeine intakes from teas. Methods: Tea infusions were prepared and caffeine contents were extracted by using chloroform and determined by UV-Vis Spectrophotometer. For lemon and carbonate addition experiments, lemon was added before the caffeine analysis and carbonate was added at the beginning. Results: Maximum caffeine contents from highest to lowest were seen in black, earl grey and green in classic teas; fennel, mint and sage in herbal teas; lemon, apple and rosehip in fruit teas. With lemon addition caffeine contents were increased except green tea and with carbonate addition caffeine contents were decreased except black and fennel tea. Daily caffeine intakes are found between 32.10% (green tea with carbonate) -77.20% (black tea with lemon), 1.85% (sage tea with carbonate) -4.05% (fennel tea with lemon) and 2.10% (rosehip with carbonate) -4.00% (lemon tea with lemon) in classic, herbal and fruit teas, respectively. Conclusion: The significance of this study indicates that herbal and fruit teas contain caffeine, which is assumed zero in literature. The caffeine amount of herbal teas (20.79 +/- 0.36-30.68 +/- 0.63 ppm) were found barely higher than the fruit teas (22.87 +/- 0.54-28.54 +/- 0.75 ppm) but daily maximum caffeine intakes were found less than 5%. The daily maximum caffeine intakes were found in the teas as 525.36 +/- 2.84-20.79 +/- 0.36 ppm, where lemon addition increased to 617.90 +/- 3.54-22.97 +/- 0.58 ppm and carbonate addition decreased to 488.54 +/- 2.05-16.84 +/- 0.28 ppm.
Keywords: Caffeine content; Caffeine intake; Carbonate; Fruit tea; Herbal tea; Lemon; PERFORMANCE; INFUSIONS; Biochemistry & Molecular Biology